Korelasi Status Gizi dengan Kesesuaian Perkembangan Anak Balita Usia 12-59 Bulan Menggunakan Skrining KPSP: Correlation Of Nutritional Status With Developmental Suitability Of Toddlers Aged 12-59 Months Using Kpsp Screening - Luluk Dwi Masruroh; Herawati Mansur (Universitas Ngudi Waluyo, 2026)
Growth and development problems in Indonesia are a significant health concern that cannot be ignored. Adequate nutrition is crucial for promoting proper growth and developmental progress in children. Analyzing the correlation between nutritional status based on anthropometry and the developmental suitability of toddlers aged 12-59 months using KPSP screening at Posyandu RW 1, Kalisongo Village, Dau District, Malang Regency. A research study using a cross-sectional approach with a correlational analytic design. The sample obtained was 31 toddlers taken using a purposive sampling technique. Primary data by taking anthropometric measurement W/H indicators, to evaluate nutritional, and the KPSP was employed to measure developmental progress. Data were analyzed using SPSS with the Spearman Rank test at a significance level of (ɑ = 0.05).The majority of toddlers' nutritional status, based on the W/H indicator, showed good nutritional status (80.6%) and age-appropriate development (71.0%). The Spearman Rank analysis showed p = 0.033 < 0.05 with a correlation coefficient (r) = 0,335. The correlation between nutritional status and appropriate development of toddlers is proven to be significant. Better nutritional status in toddlers tends to be associated with more appropriate developmental outcomes. To support optimal growth and development in toddlers, it is recommended that parents provide balanced nutrition and age-appropriate stimulation. ABSTRAK Gangguan tumbuh kembang di Indonesia adalah isu kesehatan yang tidak bisa diabaikan. Status gizi termasuk salah satu unsur yang berkontribusi terhadap proses kemajuan perkembangan balita. Tujuan penelitian yakni menganalisis korelasi antara status gizi berdasarkan antropometri dengan kesesuaian perkembangan anak balita usia 12-59 Bulan menggunakan skrining KPSP di Posyandu RW 1 Desa Kalisongo, Kecamatan Dau, Kabupaten Malang. Studi penelitian dengan pendekatan cross-sectional dalam desain analitik korelasi. Sebanyak 31 balita dijadikan sampel, diperoleh dengan menerapkan teknik purposive sampling. Data penelitian bersifat primer yang dikumpulkan dengan pengukuran antropometri indikator BB/ TB guna menetapkan status gizi anak balita, dan menggunakan instrument KPSP untuk pemeriksaan perkembangan anak balita. Analisis data dilakukan dengan SPSS melalui uji Spearman Rank pada taraf signifikasi (ɑ = 0,05). = Mayoritas gizi balita berdasarkan indikator BB/TB berada pada kategori gizi baik (80,7%) dan perkembangan normal sesuai usia (71,0%). Hasil analisis Spearman Rank didapatkan hasil p = 0,033 < 0,05 dengan koefisien korelasi (r)= 0,335. Korelasi terkait status gizi dan kesesuaian perkembangan balita terbukti signifikan. Semakin baik status gizi balita akan di ikuti dengan perkembangan yang sesuai. Untuk mendukung tumbuh kembang optimal balita, disarankan agar orang tua memberikan gizi seimbang dan stimulasi sesuai usia perkembangan